Diplomasi Publik Cina terhadap Indonesia dalam Festival Kue Bulan Tahun 2023 - Ramaldy Krisna Indradipradana; Bevita Sari; Muhammad Fauzi Abdul Rachman (Syntax Corporation Indonesia, 2024)
The Mooncake Festival is one of China's public diplomacies through cultural activities towards Indonesia. On September 27, 2023, the Chinese Government, through its Ambassador in Indonesia, held a Mooncake Festival with the theme